Noncontiguous finished genome sequences and description of Bacillus massiliglaciei, Bacillus mediterraneensis, Bacillus massilinigeriensis, Bacillus phocaeensis and Bacillus tuaregi, five new species identified by culturomics. (September 2017) - Cadoret, F.; Alou, M.T.; Afouda, P.; Traore, I.S.; Bréchard, L.; Michelle, C.; Di Pinto, F.; Andrieu, C.; Delerce, J.; Levasseur, A.; Fournier, P.-E.; Raoult, D.
Abstract: Microbial culturomics, which investigates microbial diversity by combining diversified culture conditions, matrix-assisted laser desorption/ionization time-of-flight mass spectrometry and 16S rDNA identification, allowed to identify five new species within the Bacillus genus. Bacillus massiliglaciei strain Marseille-P2600 T, Bacillus mediterraneensis strain Marseille-P2384 T, Bacillus massilinigeriensis strain Marseille-P2366 T, Bacillus tuaregi strain Marseille-P2489 T and Bacillus phocaeensis strain SIT16 T are each the type strain of the corresponding bacterial species. These strains, the genomes of which are described here, are facultative anaerobic Gram-positive bacilli. Here, we describe the main characteristics of each bacterium and present their complete genome sequence and annotation.